Theoretical and experimental study of the diastereoisomers (2S) and (2R)-naringenin-6-C-β-D-glucopyranoside obtained from Clitoria guianensis - Cruz, Állefe Barbosa; Ciribelli, Nicolas Nascimento; Cunha, Camila Luiza [UNESP]; Nascimento, Isabele Rodrigues [UNESP]; Holzbach, Juliana Cristina; Pereira, Douglas Henrique (Springer Nature, 2023)
Abstract: In this work the diastereoisomers (2S) and (2R)-naringenin-6-C-β-D-glucopyroside, isolated for the first time from Clitoria guianensis, were studied using the density functional theory. The frontier molecular orbitals and structural properties showed that the diastereoisomers exhibit the same energy gap 166.61 kcal mol−1 and structural properties different, where in the S diastereoisomer, the bond length between the chiral carbon and the phenolic group is greater (difference of 0.0126 Å). The HPLC data showed that the retention time of the S-diastereoisomer (16.7 min) is shorter than that of R, suggesting that the S compound is more polar than R. The HPLC results corroborates with the molecular electrostatic potential which showed that in the S configuration, the electronegative density was more intense overall, particularly in the glucose molecule. The reactivity indices showed that the diastereoisomers are good electrophiles and reactive species. Finally, the absolute configuration of the diastereoisomers were determined using electronic circular dichroism (ECD) spectroscopy and the theoretical spectra were similar to the experimental. Methods: All calculations of Density Functional Theory (DFT) and Time-Dependent Density Functional Theory (TDDFT) were performed using the program Gaussian 09 and the structures of the diastereoisomers were generated and analyzed using the GaussView program. The optimization and vibrational frequency calculations were performed using the functional CAM-B3LYP and 6–311 + + G(2d,2p) basis set. Conformational searches were performed for R configuration, by molecular mechanics using the MM + , MMFF, and OPLS05 force fields; the entire molecular mechanics simulation was performed using the Maestro/MacroModel software. The calculations for the simulations of the ECD spectra were performed for the eight lowest energy conformers obtained in the geometric optimization step, and the TDDFT at the CAM-B3LYP/6–311 + + G(2d,2p) theory level used. The effects of methanol and chloroform were calculated using the SMD implicit solvent model.
Keywords: Absolute configuration; Circular Dichroism; Conformational search; TDDFT